If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 5 = p + -2 Reorder the terms: 5 + 2p = p + -2 Reorder the terms: 5 + 2p = -2 + p Solving 5 + 2p = -2 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 5 + 2p + -1p = -2 + p + -1p Combine like terms: 2p + -1p = 1p 5 + 1p = -2 + p + -1p Combine like terms: p + -1p = 0 5 + 1p = -2 + 0 5 + 1p = -2 Add '-5' to each side of the equation. 5 + -5 + 1p = -2 + -5 Combine like terms: 5 + -5 = 0 0 + 1p = -2 + -5 1p = -2 + -5 Combine like terms: -2 + -5 = -7 1p = -7 Divide each side by '1'. p = -7 Simplifying p = -7
| 2(x-y+3)+3x= | | 1.6x+10=0.9x+12 | | 3x-5x+4x=10 | | 6r=-96 | | 3z=9z-24 | | 3x^7+24x^6+21x^5=0 | | v+5.8=7.63 | | A(x+3)=5x+15 | | 5(x-6)-8x=2x | | (x-4)(x+5)(x+10)(x-2)=18x^2 | | 5g+3=17 | | 3(2x+6)+2(7x-4)+10x=8x+2(x+9) | | [11-4x]-7=95-15x | | f=-19x | | t^4-3t^3-28t^2=0 | | -7.2+(-2.7)= | | 25=q-20 | | f=1+-20x-1+x | | 6x-4+2x+8=180 | | 10x-2+44=180 | | x^3-3x^2-6x-6=0 | | 3x+5+4x+1=90 | | 6a-12=2a+4 | | 2x/3-3(x-2)/5 | | 10x-6+8x+24=180 | | X-3+2x+6=90 | | (2x^-5y^2)^-2/8z= | | x^2+7c=8 | | c=14d | | (25x^(5/3))(X^(2/3)) | | g(-2)=6x^2-9x-10 | | 2.4/0.4 |